2015
DOI: 10.18203/issn.2454-2156.intjscirep20150218
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health care seeking behavior among rural population of a coastal area in South India

Abstract: <p class="abstract"><strong>Background:</strong> Understanding of health seeking behaviour (HSB) is essential to provide need based health care services to the population. Many factors like sex, age, type of illness, access to services and perceived quality of the services, influences the health seeking behavior. This study assessed the HSB among rural population of a coastal area in Tamil Nadu.</p><p class="abstract"><strong>Methods:</strong> A community based descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 8 publications
3
50
2
Order By: Relevance
“…Similar results have also been reported by Chauhan et al, in their study in a coastal area of Villupuram district in Tamil Nadu and Kumar et al in their study in Varanasi (Uttar Pradesh). 10,11 Present study reveals preference for public health care facilities 48.15% over private health care sector 31.29%, among the participants. The study also brings out Allopath as the most preferred system (55.54%), followed by Ayurveda (33.37%).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar results have also been reported by Chauhan et al, in their study in a coastal area of Villupuram district in Tamil Nadu and Kumar et al in their study in Varanasi (Uttar Pradesh). 10,11 Present study reveals preference for public health care facilities 48.15% over private health care sector 31.29%, among the participants. The study also brings out Allopath as the most preferred system (55.54%), followed by Ayurveda (33.37%).…”
Section: Discussionmentioning
confidence: 60%
“…However, Kumar et al, in their study reported musculoskeletal problems as the most common (56.5%) cause for seeking health care, followed by hypertension (34.1%), cataract or other eye related problems (23.1%) and diabetes (6.7%) etc., while Patil et al, in their study reported ARI as the most common disease (38.0 %), for seeking health care, followed by tuberculosis (30.75%), vector borne diseases like malaria and dengue, hypertension and diabetes. [10][11]13 Present study brings out that more than half (56.46%) of the study participants were aware of various available government and private health insurance schemes. However, only 19.74% of the respondents had insurance coverage, while most of them (95.8%) had subscribed to government health insurance schemes.…”
Section: Discussionmentioning
confidence: 81%
“…The steroid doses used were large enough to cause adverse drug reactions, even in the short period. Another study in Malaysia also explained the tendency of adding steroids to over‐the‐counter traditional medicines or through traditional health services, causing fears of the emergence of steroid adverse drug reactions …”
Section: Discussionmentioning
confidence: 99%
“…Various studies also showed a good percentage visiting alternative health care. 10 The decision for visiting local chemists may be due to the reason that it is accessible and care given free of cost.…”
Section: Discussionmentioning
confidence: 99%